Structural Properties and Dielectric Hysteresis of Molecular Organic Ferroelectric Grown from Different Solvents - Elena Balashova (MDPI AG, 2021)
A comparative analysis of crystal structure, Raman spectra, and dielectric hysteresis loops was carried out for organic ferroelectric crystals of 2-methylbenzimidazole (MBI) grown from ethanol (MBIet), acetone (MBIac), deuterated acetone (MBId-ac), or prepared by sublimation from gas phase (MBIgas). Raman spectroscopy shows identical frequencies of molecular vibrations in all studied crystals, proving the same molecular structure. At the same time, a detailed analysis of the asymmetry of the powder XRD reflection profiles indicates the presence of nano-scaled regions with the same MBI symmetry and crystal structure but slightly different sizes and unit cell parameters. The formation of the MBI modifications is associated with possible penetration of solvent molecules into the voids of the MBI crystal structure. Dielectric hysteresis loops in MBIet and MBId-ac crystals at room temperature demonstrate significantly different values of coercive fields Ec. Analysis of hysteresis loops within the framework of the Kolmogorov-Avrami-Ishibashi (KAI) model shows that the polarization switching in MBId-ac occurs much faster than in MBIet crystals, which in the KAI model is associated with different values of the characteristic frequency ω0 and the activation field Ea of the domains wall motion.